Konsentrasi Aman Kurkumin dan PGV-0 terhadap Sel Vero Berdasarkan Hasil Uji Sitotoksik - Marbawati, Dewi; Sarjiman, Sarjiman (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2015)
Curcumin (1,7-bis(3-methoxyphenyl 4'hidroksi) -1.6 heptadien, 3,5-dione) is the yellow pigment of Curcuma longa. Curcumin has various biological activities such as antioxidant, antibacterial, antifungal, antiprotozoal and antivirus. Various benefits of curcumin can not be separated from the weakness which is not stable to pH and light. Pentagamavunon-0 (PGV-0) were made by changing the β diketone group on cluster analog of curcumin into monoketon while eliminating active methylene group so it is more stable to pH and light. PGV-0 also has potential as a stronger antioxidant and antiinflammatory agent than other curcumin analogues. The objective of this research was to determine the safe concentrations of curcumin and PGV-0 on vero cells due to the increased use of the two compounds through the cytotoxic test. This research includes experimental research. Cytotoxic test performed with microculture tetrazolium technique (MTT) method. Use of MTT to evaluate the cytotoxic is based on changes of tetrazolium salt into formazan crystals by mitochondrial enzyme succinate dehydrogenase with the help of cellular NADH. The results showed that the safe concentrations of curcumin and PGV-0 on vero cells respectively are 6.25 and 1.5625 ppm. Based on the cytotoxic test the secure concentration of curcumin was higher than PGV-0.